2000
DOI: 10.1063/1.874006
|View full text |Cite
|
Sign up to set email alerts
|

Response of internal transport barriers to central electron heating and current drive on ASDEX Upgrade

Abstract: Internal transport barriers with the central electron temperature as large as the central ion temperature both in excess of 10 keV have been achieved in the Axi-symmetric divertor experiment (ASDEX Upgrade) [H. Vernickel et al., J. Nucl. Mater. 128, 71 (1984)]. By applying central electron cyclotron heating and current drive to negative central shear discharges, established by neutral beam heating in the current ramp, the core electron temperatures could be raised by more than a factor of 2. Despite the fivefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 12 publications
4
36
0
Order By: Relevance
“…It is noted here that since in tokamaks M θ < 0.1 the flow term in (2) is perturbative around the "static" equilibrium M θ = 0. Also, the choice q min = 2 was made because according to experimental evidence for q min < 2 strong MHD activity destroys confinement possibly due to a double tearing mode [18]. A similar result was found numerically for one-dimensional cylindrical equilibria with hollow currents in Ref.…”
Section: Resultssupporting
confidence: 56%
“…It is noted here that since in tokamaks M θ < 0.1 the flow term in (2) is perturbative around the "static" equilibrium M θ = 0. Also, the choice q min = 2 was made because according to experimental evidence for q min < 2 strong MHD activity destroys confinement possibly due to a double tearing mode [18]. A similar result was found numerically for one-dimensional cylindrical equilibria with hollow currents in Ref.…”
Section: Resultssupporting
confidence: 56%
“…The choice q min ≥ 2 was made because according to experimental evidence for q min < 2 strong MHD activity destroys confinement possibly due to a double tearing mode [19]. A similar result was found numerically for one-dimensional cylindrical equilibria with hollow currents in [20].…”
Section: Resultssupporting
confidence: 51%
“…Neglecting in the Hall-MHD momentum equation the convective flow term (which for the case under consideration corresponds to M θ = 0), the term j × B in (19) can be expressed in terms of the total pressure gradient:…”
Section: Two-fluid Cylindrical Equilibria With Reversed Magnetic Shearmentioning
confidence: 99%
“…the magnetic shearŝ. The effects of the latter on plasma microturbulence has been the subject of numerous experimental [19][20][21][22][23] , theoretical 24 , as well as numerical [25][26][27][28] studies. In this context, it was also found that negative magnetic shear can help improve the plasma confinement in a tokamak by decreasing the level of turbulence.…”
Section: B Robustness While Varying the Temperature Gradientmentioning
confidence: 99%